Norway: Shadow WTO agricultural domestic support notifications - Gaasland, Ivar; Garcia, Robert; Vårdal, Erling (International Food Policy Research Institute, 2008)
As a result of the Uruguay round, Norway was committed to reducing its domestic support for agriculture, in particular its aggregate measurement of support (AMS), which was to be reduced by 20 percent. We show that Norway has complied with its WTO commitments. However, Norway’s AMS and total support have remained stable during 1995-2007, implying that the reduction commitment amounted to no more than reducing the “water under” an inflated AMS bound rate. Thus, the reductions in domestic support have neither affected agricultural policy nor the programs implemented. In fact, Norway has even managed to expand agricultural output relative to the 1986-1988 base upon which agricultural reforms are measured under the Uruguay round agricultural agreement. We analyze the implications of the proposed modalities for reduction commitments on agriculture under the Doha round of WTO negotiations in the Norwegian context. Simulation modeling is conducted to examine the consequences for the Norwegian agricultural sector based on the proposed reduction commitment scenarios. We find that Norway will be able to sustain a high level of agricultural support, thereby maintaining its current agricultural activity and production levels. To achieve this, however, Norway will have to change the composition of domestic support from market price support, paid for by consumers in the form of higher prices, to budgetary support. Market price support will be lower because of lower levels of tariff protection, but this can be offset by exploiting the scope for green box support.